(untitled) (Clinics, 2015)
OBJECTIVE:In this study, we aimed to compare the cardiovascular risk factors that might be associated with inflammation, atherosclerosis and metabolic syndrome between hemodialysis and peritoneal dialysis patients.METHODS:Fifty hemodialysis and 50 peritoneal dialysis patients who had been receiving dialysis therapy for at least one year were included in the study. Venous blood samples were taken after 12 hours of fasting, and serum glucose, triglyceride, low-density lipoprotein (LDL)-cholesterol, high-density lipoprotein (HDL)-cholesterol, C-reactive protein, fibrinogen and homocysteine levels were measured. The presence of atherosclerotic plaques in the carotid artery was evaluated by carotid Doppler ultrasound. These data were analyzed by Student’s t test, the chi-square test and the Mann-Whitney U test, as appropriate.RESULTS:No difference was found between the hemodialysis (n=50) and peritoneal dialysis (n=50) patient groups regarding mean age, gender distribution, body mass index or dialysis duration (p=0.269, 0.683, 0.426, and 0.052, respectively). LDL-cholesterol, fibrinogen and homocysteine levels were significantly higher in peritoneal dialysis patients (p=0.006, 0.001, and 0.002, respectively). In patients with diabetes mellitus (n=17) who were undergoing renal replacement therapy, LDL-cholesterol and fibrinogen levels were significantly higher than in patients without diabetes mellitus who were undergoing renal replacement therapy (p=0.001 and 0.004, respectively).CONCLUSION:In our study, cardiovascular risk factors (especially LDL-cholesterol) were more frequent in peritoneal dialysis patients than in hemodialysis patients.